Infliximab treatment in Psoriatic Arthritis: our experience - Troise Rioda, W.; Adorni, G. (Acta Biomedica Atenei Parmensis, 2006)
The aim of this work was to give clinical practice recommendations on the use of tumour necrosis factor blocking agents in psoriatic arthritis, underlining the pathogenetic mechanism of this condition and its articular and dermatologic manifestations.We retrace the stages leading to the therapeutic indications of biological agents that are presently used in the treatment of psoriatic arthritis: Entanercept,Adalimumab, Infliximab. We also report our personal experience describing an emblematic case of a patient with psoriatic arthritis in which a decisive regression of joint/skin involvement was obtained with Infliximab treatment.